2007
DOI: 10.1007/s10570-007-9189-x
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose swelling by protic solvents: which properties of the biopolymer and the solvent matter?

Abstract: The question posed in the title has been addressed by studying the swelling of celluloses at 20°C by twenty protic solvents, including water; linear-and branched-chain aliphatic alcohols; unsaturated aliphatic alcohols, and alkoxyalcohols. The biopolymers investigated included microcrystalline cellulose, MC, native and never-dried mercerized cotton cellulose, cotton and M-cotton, and native and never-dried mercerized eucalyptus cellulose, eucalyptus and M-eucalyptus, respectively. In most cases, better correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 71 publications
1
54
0
7
Order By: Relevance
“…Data recalculated from ref. [7]. curs in these probes, from the phenolate oxygen to the heterocyclic nitrogen; the corresponding CT band is sensitive to the solvent, i.e., is solvatochromic [8].…”
Section: Understanding Solvation In Pure Solventsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data recalculated from ref. [7]. curs in these probes, from the phenolate oxygen to the heterocyclic nitrogen; the corresponding CT band is sensitive to the solvent, i.e., is solvatochromic [8].…”
Section: Understanding Solvation In Pure Solventsmentioning
confidence: 99%
“…Additionally, this treatment leads to the transformation of cellulose I to cellulose II, the latter has less inter-crystalline hydrogen bonding [6]. Thus the supramolecular structure of mercerized cellulose is more accessible to the solvent; this leads to less sensitivity to solvent properties, relative to its native counterpart [7].…”
Section: © 2009 Iupac Pure and Applied Chemistry 81 697-707mentioning
confidence: 99%
See 1 more Smart Citation
“…26 Our results have shown that the use of solvatochormic parameters in order to describe the dependence of cellulose swelling on solvent properties resulted in better correlations coefficients, as compared with those based on Gutmann´s, or Hildebrand´s solubility parameters. 27 In fact, we were able to correlate the swelling of twenty eight protic and aprotic solvents simultaneously with the solvent molar volume, b S , and p* S (a S was excluded because the dipolar aprotic solvents carry no acidic hydrogens). 27 This is remarkable because previous work on swelling has either used a very limited number of solvents, or employed solvents of the same nature, either protic or aprotic.…”
mentioning
confidence: 95%
“…27 In fact, we were able to correlate the swelling of twenty eight protic and aprotic solvents simultaneously with the solvent molar volume, b S , and p* S (a S was excluded because the dipolar aprotic solvents carry no acidic hydrogens). 27 This is remarkable because previous work on swelling has either used a very limited number of solvents, or employed solvents of the same nature, either protic or aprotic. 28 This success indicates that the same solute-solvent interactions mechanisms are relevant to probe solvation and cellulose swelling.…”
mentioning
confidence: 95%